2018
DOI: 10.1093/jxb/ery101
|View full text |Cite
|
Sign up to set email alerts
|

Two transcription factors TaPpm1 and TaPpb1 co-regulate anthocyanin biosynthesis in purple pericarps of wheat

Abstract: Two genes controlling the purple pericarp trait in wheat, TaPpm1 and TaPpb1, are identified and the mechanism by which they co-regulate anthocyanin synthesis is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 63 publications
(84 reference statements)
4
85
0
3
Order By: Relevance
“…In another study, Li et al [171] isolated an MYB transcription factor gene, TaMYB3, localised on chromosome 4BL which induces anthocyanin synthesis in the pericarp cells. Recently, Jiang et al [172] characterised two transcription factors: TaPpm1 (purple pericarp-MYB 1) and TaPpb1 (purple pericarp-bHLH 1) in wheat, and it was demonstrated that the interaction of TaPpm1 and TaPpb1 co-regulates the synthesis of anthocyanin in pericarps.…”
Section: Genetic Basis Of Purple Coloured Wheat Grainsmentioning
confidence: 99%
“…In another study, Li et al [171] isolated an MYB transcription factor gene, TaMYB3, localised on chromosome 4BL which induces anthocyanin synthesis in the pericarp cells. Recently, Jiang et al [172] characterised two transcription factors: TaPpm1 (purple pericarp-MYB 1) and TaPpb1 (purple pericarp-bHLH 1) in wheat, and it was demonstrated that the interaction of TaPpm1 and TaPpb1 co-regulates the synthesis of anthocyanin in pericarps.…”
Section: Genetic Basis Of Purple Coloured Wheat Grainsmentioning
confidence: 99%
“…Pp3 (mapped to chromosome 2A) encodes a bHLH transcription factor (Shoeva et al, 2014). The Pp-1 genes (7A, 7B, 7D) encode R2R3-MYB-type transcription factors (Jiang et al, 2018). The Ba genes responsible for blue aleurone were transferred into cultivated wheat varieties from distant relatives such as Thinopyrum ponticum, Th.…”
Section: Regulation Of Anthocyanin Biosynthesis In Wheat Pericarpmentioning
confidence: 99%
“…Based on the high-throughput screening and stringent screening pressure, many researches have obtained candidate prey proteins by yeast one-and two-hybrid assays, like in wheat [3,4], Arabidopsis [5], rice [6], populus [7], kiwifruit [8] and so on. Moreover, increasing numbers of studies focused on improving the screening efficiency, saving time and decreasing the cost required to identify target molecules in yeast one-and two-hybrid system assays [9,10].…”
Section: Introductionmentioning
confidence: 99%